SPPL-BASED ASSESSMENT OF PUBLIC LIBRARIES - Laspinas, Marilyn L. (European Scientific Journal, ESJ, 2014)
This study assessed the public libraries based on Standard of Philippine Public Libraries (SPPL) in Region VII for fiscal year 2010. Specifically, it evaluates the status of public libraries in terms of: mission, goals, and objectives; administration; human resources; library collection; services and utilization; physical facilities; IT facilities and services; financial resources; and linkages and networking. The study employed descriptive survey method, using researcher-made survey questionnaires in collecting detailed and factual information of 39 public libraries. Results showed that development of library mission, goals and objectives are the responsibility of the library personnel in consultation with the LGU officials. Both city and municipal libraries met the standard in hiring support staff but BS in employing professional librarians. Hence, both libraries are in conformity with the standard considering the inputs of computers and internet connection. Furthermore, financial resources of the city libraries were well funded from sponsors, private donation and funds for city local officials. Finally, linkages and networking of city and municipal libraries were rated very good as they initiated to secure grants, scaling up concepts and sharing of knowledge. Thus, public libraries will eventually and hopefully become a channel of communication to advance literacy rate for all Filipinos nationwide.